De Novo versus secondary metastatic EGFR-mutated non-small-cell lung cancer - Bozorgmehr, Farastuk; Kazdal, Daniel; Chung, Inn; Kirchner, Martina; Magios, Nikolaus; Kriegsmann, Mark; Allgäuer, Michael; Klotz, Laura Valentina; Muley, Thomas; El-Shafie, Rami; Fischer, Jürgen; Faehling, Martin; et al. (Frontiers in oncology, 2021)
Background: Metastatic epidermal growth factor receptor-mutated (EGFR)+ non-small-cell lung cancer (NSCLC) can present de novo or following previous nonmetastatic disease ("secondary"). Potential differences between these two patient subsets are unclear at present. Methods: We retrospectively analyzed characteristics of tyrosine kinase inhibitor (TKI)-treated patients with de novo vs. secondary metastatic EGFR+ NSCLC until December 2019 (n=401). Results: De novo metastatic disease was 4x more frequent than secondary (n=83/401), but no significant differences were noted regarding age (median 66 vs. 70 years), sex (65% vs. 65% females), smoking history (67% vs. 62% never/light-smokers), and histology (both greater than 95% adenocarcinoma). Patients with secondary metastatic disease showed a better ECOG performance status (PS 0-1 67%-32% vs. 46% 52%, p=0.003), fewer metastatic sites (mean 1.3 vs. 2.0, p less than 0.001), and less frequent brain involvement (16% vs. 28%, p=0.022) at the time of stage IV diagnosis. Progression-free survival (PFS) under TKI (median 17 for secondary vs. 12 months for de novo, p=0.26) and overall survival (OS, 29 vs. 25 months, respectively, p=0.47) were comparable. EGFR alterations (55% vs. 60% exon 19 deletions), TP53 mutation rate at baseline (47% vs. 43%, n=262), and T790M positivity at the time of TKI failure (51% vs. 56%, n=193) were also similar. OS according to differing characteristics, e.g. presence or absence of brain metastases (19-20 or 30-31 months, respectively, p=0.001), and ECOG PS 0 or 1 or 2 (32-34 or 20-23 or 5-7 months, respectively, p less than 0.001), were almost identical for de novo and secondary metastatic disease. Conclusions: Despite the survival advantage reported in the pre-TKI era for relapsed NSCLC, molecular features and outcome of TKI-treated metastatic EGFR+ tumors are currently independent of preceding nonmetastatic disease. This simplifies design of outcome studies and can assist prognostic considerations in everyday management of patients with secondary metastatic EGFR+ tumors.